Менопауза: сучасні уявлення про безпеку та ефективність лікування - Кирилюк, М. Л. (Clinical Endocrinology and Endocrine Surgery, 2014)
In lectures presented data on pathogenesis, clinical manifestations and current treatment of menopausal syndrome. Questions of safety of hormone replacement therapy are being discussed.